2018
DOI: 10.25077/elevate.1.1.40-45.2018
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal mother: Knowledge and attitude towards Neonatal Jaundice (NNJ)

Abstract: Neonatal jaundice (NNJ) is a pathological situation where an imbalance between bilirubin production and excretion is present due to a multitude of factors.  The objective of this study is to identify the number of post-natal mothers who had received education and their attitude on neonatal jaundice.  A cross-sectional design was carried out among 131 posts natal mother. The questionnaire was given to the respondents. Results show there is a significant relationship between knowledge and attitude towards neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…19 Studies done in Africa and other developing countries also showed that the knowledge, attitude and practice of mothers to NNJ is poor. [20][21][22][23] There was an association between knowledge, attitude and practice with some demographic factors like age, occupation, religion, parity, ethnicity and level of education. 15,20,[23][24][25][26] There seems to be a gap in the knowledge on NNJ by some health workers who are the major source of information to mothers.…”
Section: Introductionmentioning
confidence: 99%
“…19 Studies done in Africa and other developing countries also showed that the knowledge, attitude and practice of mothers to NNJ is poor. [20][21][22][23] There was an association between knowledge, attitude and practice with some demographic factors like age, occupation, religion, parity, ethnicity and level of education. 15,20,[23][24][25][26] There seems to be a gap in the knowledge on NNJ by some health workers who are the major source of information to mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers' knowledge on these interventions could equally be attributed to the health education given to them by the health workers, and other civil society organizations that are into health education of communities. However, these stated interventions were found to relate to studies of Khalesi & Rakhshani,[31], Benova et al, [44], and Said et al, [45], which equally mentioned some of these interventions as treatment and management options for NNJ.…”
Section: Sources Of Information About Nnj Among Puerperal Mothersmentioning
confidence: 99%
“…Poor knowledge and lack of better appreciation of NNJ is a precursor for poor clinical decisions including treat or not to treat, late medical care, and poor outcomes ( Ayete-Nyampong & Udofia, 2020 ; Demis et al, 2021 ; Hannon et al, 2001 ; Opara et al, 2014 ). A decade and half literature on NNJ shows that much research focus on maternal knowledge on NNJ with little focus on healthcare providers ( Adoba et al, 2018 ; Demis et al, 2021 ; Egube et al, 2013 ; Goodman et al, 2015 ; Lake et al, 2019 ; Ogunfowora & Daniel, 2006; Navabi et al, 2020 ; Said et al, 2018 ; Salia et al, 2021 ). However, there exist some studies on the knowledge of nurses and midwives on NNJ at varying levels (Alemu et al, 2011; Ekanem & Young, 1994 ; Ogunfowora & Daniel, 2006; Opara et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%